2019
DOI: 10.1136/bcr-2019-232987
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase 3 (PR3)-antineutrophil cytoplasmic antibody (ANCA)-associated vasculitic neuropathy in diffuse cutaneous systemic sclerosis: a rare duo

Abstract: Systemic sclerosis (SSc) is characterised by non-inflammatory vasculopathy, autoimmunity and widespread fibrosis. While the presence of antineutrophil cytoplasmic antibodies (ANCAs) has been reported in SSc, their association with ANCA-associated vasculitis is exceedingly rare. Myeloperoxidase ANCA is more common than proteinase-3 ANCA, and glomerulonephritis is the most common clinical presentation of ANCA-associated vasculitis in SSc. ANCAs have been associated with the adverse disease outcomes in SSc, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Another case of SSc and ANCA associated vasculitis reported by Radwan et al of a 65-year-old man with diffuse cutaneous SSc presenting with new-onset peripheral neuropathy. The patient had a positive PR3 and cytoplasmic ANCA, and histopathology confirmed an inflammatory vasculitic neuropathy [12] . On the other hand, overlap between PAN and SSc was very rarely reported in SSc.…”
Section: Discussionmentioning
confidence: 92%
“…Another case of SSc and ANCA associated vasculitis reported by Radwan et al of a 65-year-old man with diffuse cutaneous SSc presenting with new-onset peripheral neuropathy. The patient had a positive PR3 and cytoplasmic ANCA, and histopathology confirmed an inflammatory vasculitic neuropathy [12] . On the other hand, overlap between PAN and SSc was very rarely reported in SSc.…”
Section: Discussionmentioning
confidence: 92%
“…We identified six papers describing the clinical features of 12 SSc patients with ANCA‐associated neuropathy (Table 1). 2,3,5–8 In all the reported cases, the SSc diagnosis preceded the ANCA‐associated neuropathy diagnosis. Positive results for anti‐Scl‐70 antibody were observed in five patients (5/12).…”
Section: Discussionmentioning
confidence: 98%
“…Second, ANCA positivity was found to be more closely related to ILD in SSc patients, regardless of AAV classification [ 6 ]. Third, proteinase 3 (PR3)-ANCA was shown to be associated with neuropathy in SSc patients, although it was not classified as having SSc-AAV-OS [ 7 ]. In addition, our previous study on ANCA positivity in Korean patients with SSc revealed that the detection rate of ANCA was 20.3%, and 1.7% of study subjects could finally be reclassified as having SSc-AAV-OS [ 8 ].…”
Section: Introductionmentioning
confidence: 99%